Politik Memori Sosok Andi Depu dalam Konstelasi Politik di Polewali MandarPolitik Memori Sosok Andi Depu dalam Konstelasi Politik di Polewali Mandar - Hamsah, Muh. Ilham Noer; Rasyid, Suraya (Rihlah: Jurnal Sejarah dan Kebudayaan, 2024)
This article is research that examines the problem of collective memory and the manifestation of material objects in the figure of Andi Depu in Mandar society. Apart from that, this article will also focus on the political actualization of the memory of the figure of Andi Depu by the Masdar Dynasty in the political constellation in Polewali Mandar Regency. By using the library research method to collect important data relevant to the research topic, using a sociological and political approach to see and describe the socio-cultural conditions that occur in Mandar, especially the Polewali Mandar district area. The results of this research show that there is identity politics in the political activities carried out by the Masdar dynasty, especially in the depiction of the figure of Andi Depu in several of his policies while he was Regent in Polewali Mandar Regency.